Pedestrian Knowledge, Attitudes and Practices in Urban Walking Environments Among Bahir Dar, Gondar and Dessie Towns, Ethiopia - Mekonnen, Fesseha Hailu; Haile, Fentanesh (Ethiopian Journal of Social Sciences, 2018)
Even though walking is one of  the most important modes of transport, it is often undervalued by urban planners and policy makers. This study aimed at assessing pedestrians’ knowledge on sidewalk utilization and their attitudes toward sidewalk facilities. A cross-sectional data on pedestrians’ knowledge, attitudes and practices were collected from three towns. Using population proportion sampling procedure the sample size for the study was determined to be 600. The 95% degree of confidence was also used. Respondents were asked to answer three groups of questions focusing on their knowledge, attitudes and practices related to sidewalks. Findings show that respondents have adequate knowledge on sidewalk facilities’ utilization, but they are poor practical implementers. There was no statistically significant difference at the p>.05 level in attitude scores for three significances: F (2,432) =4.6. Proper management of the available sidewalk facilities should be given priority by each city administrations. A more detailed study of each city’s traffic management and planning could bring long term solutions for pedestrian problems.